A Cross-Sectional Study of the Factors Affecting on Turnover Intention of Nurses - Dehghannezhad, Javad; Ebrahimzadeh, Farzad; Dadashzadeh, Abbas; Ghafourifard, Mansour; Rahmani, Azad; Hassankhani, Hadi; Behshid, Mozhgan; Valizadeh, Fariba (Advances in Nursing & Midwifery, 2023)
Introduction: Nurses are the largest group of health care professionals in health care systems. One of the main challenges of health care systems is the shortage of qualified nurses and Nurses’ intention to leave the profession is one of the key issues in nursing all over the world. The aim of this study was to investigate the factors affecting nurses' turnover in Iran. Methods: This descriptive cross-sectional study was conducted in the School of Nursing and Midwifery, Tabriz, Iran, in 2018. In this study, 500 nurses were selected Convenience sampling method was used for recruitments of samples. Data were collected using Anticipated Turnover Scale (ATC) and Measurement of the intention to leave the profession in nurses and were analyzed using SPSS (version 16). Results: The results showed that the overall score of the Anticipated Turnover Scale was 4.04 ± 0.53. Factors affecting nurses intention to leave included organizational (3.42 ± 0.66), professional (3.05 ± 0.55), faily-work conflict (3.52 ± 0.82) and economic (3.82 ± 0.80) factors. The results showed a significant differences between the mean score of turnover intention and the variables of nurses gender (P= 0.006, T=2.75) and work experience (P= 0.001, F=5.54). Conclusions: Reduction of economic problems and conflict between family and work makenurses stay in the health care system. Also, nurse managers should consider the needs of nurses based on age, gender, work experience and cultural and social differences.